Conceptual informatiom as a process of language manipulation of information in cognitive linguistics - Bektashev Otabek Kodiralievich (Research Parks Publishing LLC, 2020)
The article deals with realization of conceptual information as a process of language manipulation of information in cognitive linguistics. Besides that it has been analyzed cognitive informations as a specific human information acquiring in the experience of cognating in perception of the world.